Shadow banking, financial regulation and animal spirits: An ACE approach - Sebastian Krug; Hans-Werner Wohltmann (Kiel University, Department of Economics, 2016)
Over the past decades, the framework for financing has experienced a fundamental shift from traditional bank lending towards a broader market-based financing of financial assets. As a consequence, regulated banks increasingly focus on coping with regulatory requirements meaning that the resulting funding gap for the real economy is left to the unregulated part of the financial system, i.e. to shadow banks highly relying on securitization and repos. Unfortunately, economic history has shown that unregulated financial intermediation exposes the economy to destabilizing externalities in terms of excessive systemic risk. The arising question is now whether and how it is possible to internalize these externalities via financial regulation. We aim to shed light on this issue by using an agent-based computational macro-model as experimental lab. The model is augmented with a shadow banking sector representing an alternative investment opportunity for the real sector which shows animal spirit-like, i.e. highly pro-cyclical and myopic, behavior in its investment decision. We find that an unilateral inclusion of shadow banks into the regulatory framework, i.e. without access to central bank liquidity, has negative effects on monetary policy goals, significantly increases the volatility in growth rates and that its disrupting character materializes in increasing default rates and a higher volatility in the credit-to-GDP gap. However, experiments with a full inclusion, i.e. with access to a lender of last resort, lead to superior outcomes relative to the benchmark without shadow banking activity. Moreover, our results highlight the central role of the access to contagion-free, alternative sources of liquidity within the shadow banking sector.
Keywords: E44; E50; G01; G28; C63; 330; Shadow Banking; Financial Stability; Monetary Economics; Macroprudential Policy; Financial Regulation; Agent-based Macroeconomics